2009
DOI: 10.1080/15376510903121145
|View full text |Cite
|
Sign up to set email alerts
|

Role of some Egyptian medicinal plants against liver and kidney toxicity induced by cadmium chloride

Abstract: The present study was designed to evaluate the protective effect of some local medicinal plants against liver and kidney toxicity induced by cadmium chloride. Methanolic extracts of Acacia nilotica and Retama raetam were used in this study. Furthermore, histopathological and histochemical investigations were done. Cadmium chloride caused a significant increase in serum AST, ALT, ALP, bilirubin, urea, and creatinine, cholesterol, LDL, triglycerides, and HDL levels Administration of Acacia nilotica and Retama ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
9
1
2
Order By: Relevance
“…These findings suggest that subacute ingestion of RR-methanolic extract at relatively high doses is nephrotoxic in rats. This is in contrast with previous studies that suggested the ability of the methanolic extract of the powder of the dried seeds of RR to protect against gentamicin-induced nephrotoxicity 34 and cadmium chloride-induced hepato-and nephrotoxicities 15 in rats. The apparent differences can be explained on the basis of the differences in method of extraction, the dosing regimen, as well as the differences in the part used, and environment of RR which might affect the presence and/or concentration of the active constituents.…”
Section: Discussioncontrasting
confidence: 83%
“…These findings suggest that subacute ingestion of RR-methanolic extract at relatively high doses is nephrotoxic in rats. This is in contrast with previous studies that suggested the ability of the methanolic extract of the powder of the dried seeds of RR to protect against gentamicin-induced nephrotoxicity 34 and cadmium chloride-induced hepato-and nephrotoxicities 15 in rats. The apparent differences can be explained on the basis of the differences in method of extraction, the dosing regimen, as well as the differences in the part used, and environment of RR which might affect the presence and/or concentration of the active constituents.…”
Section: Discussioncontrasting
confidence: 83%
“…According to Bossuyt et al [37], an additional peak in the α 2 -globulins fraction may be the result of an excessive concentration of triglycerides in the serum. Koriem et al [38] observed a significant increase in the concentration of cholesterol, low-density lipoproteins and triglycerides in the blood serum of rats exposed to Cd. In these studies, changes identified in the α 2 -globulins fraction may result from the effect of Cd on the protein profile.…”
Section: Changes In the Protein Profile Shapementioning
confidence: 98%
“…Mivel a kadmium legfőképpen a májban és a vesében akkumulálódik, ezért fontos szemügyre venni a receptekben szereplő Acacia nilotica L., nílusi akácia (Mimosaceae) pozitív hatásait a kadmiummérgezés tüneteinek enyhítésében. A nílusi akáciában található egyes flavonoidok (kromonszármazékok) képesek arra, hogy két vagy három vegyér-tékű fémionokkal (Cd 2+ ) fémkomplexet képezzenek, így mérsékeljék az akkumulálódott fémek szabadgyökös reakcióit [19]. Ez a jelenség is indokolja, hogy az akácia helyet kapjon a májjal kapcsolatos receptekben.…”
Section: Flavonoidokunclassified